Characterization Linguistic policies around Peruvian Sign Language (PSL) - Galloso Cossios, Rodrigo Saniel (2022)
The main objective of this article is to analyze the linguistic policies regarding a viso-gestural language: Peruvian Sign Language or LSP. Currently, the Ministry of Culture oversees the linguistic policies of the country’s native languages; however, although LSP could be considered native, it is not and does not fall under the linguistic policies of the Ministry of Culture. On the other hand, the Ministry of Women oversees the LSP language policies; however, it has not worked much in favor of the LSP. The article concludes that if the LSP were considered a native language, many gaps in language policies could be resolved.